HEMOGLOBIN LEVELS IN OBSTETRIC POPULATION - M. Moshirfatemi; M. Faghihi; M.R. Salimi; A. Banan; Khatibi (Tehran University of Medical Sciences, 1976)
Hemoglobin values in 9550 mothers delivered in the OB. & GYN. Dept. of Amin medical center were studied. Hemoglobin levels of less than 11gr/100ml which is usually considered to be to the lower limit of normal for pregnancy were found in 2410 patient (25.3%) this rate has been recorded to be 19-30 percent in the U.S.A., 36 percent in Western Venezuela, 57.4 percent in India and about 80 percent in Bengali. In 4740 individuals (49.6%) the hemoglobin levels were below 12gr/100ml which is similar to the rates recorded for American women. The rate of anemia somewhat rises in our series with increasing number of pregnancies.